COUNSELING ON THE IMPORTANCE OF FINANCIAL BOOKKEEPING IN MSMES BOJA VILLAGE, KENDAL CENTRAL JAVA: PENYULUHAN PENTINGNYA PENCATATAN PEMBUKUAN KEUANGAN PADA UMKM DESA BOJA, KEC BOJA , KAB KENDAL JAWA TENGAH - Yuyun Ristianawati; Astohar Astohar; Noorsalim Noorsalim (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
The role of the financial report in the MSME business unit is vital; this is a means for MSME s in managing their finances. The reporting information in this financial report assesses the financial performance of MSMEs for their management and to account for the funds they manage. For MSMEs in Boja village, Boja village, Boja district, Kendal district, financial bookkeeping has an important role and is needed to develop business units, formulate plans year, and evaluate business units managed by MSMEs in Boja village